Pengaruh Pelatihan Kerja, Dan Reward Terhadap Kinerja Karyawan - Rima Zamilah; Askolani Askolani; Rita Tri Yusnita (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study is to determine and analyze the effect of job training, rewards, and employee performance at Hotel Santika Tasikmalaya. The research method used is a quantitative method with a survey approach, the data obtained directly through a questionnaire to 65 respondents taken from Hotel Santika Tasikmalaya employees. Sampling used saturated sampling technique and the analytical method used in this study was multiple linear regression analysis using SPSS 25 software. Based on the results of the study, job training variables were included in the good classification, reward variables were included in the good classification and employee performance was included in the good classification. The test results show that job training and rewards simultaneously have a significant effect on employee performance at Hotel Santika Tasikmalaya. Job training partially has a significant effect on employee performance and reward partially has no significant effect on employee performance.